Incidence and patterns of hearing loss associated with the consistent use of mobile telephone among adolescents in Ibadan, Nigeria (2017)
There has been an increased incidence of hearing -related difficulty due to consistent use of mobile phones, particularly those with multiplicity of functions for continued calls and music playing functions. Thus, this study investigated the incidence and patterns of hearing loss associated with the consistent use of mobile telephone among adolescents in Ibadan Metropolis. The study adopted an ex-post facto research design, sampling 500 adolescents through the use of Hearing and Mobile Telephony Questionnaire (HMTQ). Frequency counts and percentage were employed to answer the three (3) research questions raised. The findings revealed that 84.6% were without hearing loss as against 15.4% of the participants who presented with different degrees and patterns of hearing loss. Forty two (54.55%) were males, while 35(45.45%) were the female participants who presented with hearing loss. 423 participants claimed having normal hearing ability even with the consistent use of mobile phone, while 43 of the participants presented with low-frequency hearing loss at left ear, and 46participants were found with high-frequency hearing loss at the right ear. Further, it was established that people should be enlightened on the dangers of consistent use of mobile telephone to hearing. Therefore,, it is recommended that mobile phone should not be used for a long period of time, even when used for calls, and leisure such as music playing functions. The youths should be dissuaded from continued use of ear-piece during leisure. Also, adolescents should go for hearing assessment on a regular basis so as to detect early any changes along their auditory performance